2004
DOI: 10.2343/geochemj.38.215
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Paleoproterozoic metasedimentary rocks from the Birim diamondiferous field, southern Ghana: Implications for provenance and crustal evolution at the Archean-Proterozoic boundary

Abstract: Metagraywackes and metapelites from the Paleoproterozoic Birimian Supergroup in the Birim diamondiferous field, southern Ghana, were analyzed for their major and trace element contents. Compared to early Proterozoic crust, the metasedimentary rocks are enriched in ferromagnesian elements but depleted in rare earth elements (REE), high field strength elements (HFSE) (with exception of Zr), and Th. They show REE patterns similar to their Archean counterparts. The chemical data indicate that the sediments were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 34 publications
6
35
0
6
Order By: Relevance
“…The volcaniclastic debris was perhaps derived from volcanogenic highlands along an active island arc or from a continental margin. This interpretation is supported by data presented in Leube et al (1990), Taylor et al (1992), Asiedu et al (2004), andFeybesse et al (2006). Leube et al (1990) suggested the magmatism and sedimentation in the Birimian to be coeval.…”
Section: Metasediment Classification and Provenancesupporting
confidence: 60%
“…The volcaniclastic debris was perhaps derived from volcanogenic highlands along an active island arc or from a continental margin. This interpretation is supported by data presented in Leube et al (1990), Taylor et al (1992), Asiedu et al (2004), andFeybesse et al (2006). Leube et al (1990) suggested the magmatism and sedimentation in the Birimian to be coeval.…”
Section: Metasediment Classification and Provenancesupporting
confidence: 60%
“…11) indica que las rocas estudiadas (en particular las fangolitas) tienen afinidad con las rocas ígneas calcoalcalinas. En tanto, en los diagramas Co/ Th versus La/Sc (Gu et al, 2002) y Cr/Th versus Th/Sc (Asiedu et al, 2004) (Figs. 12A y B) las sedimentitas se distribuyen en áreas de las rocas félsicas, con relativamente elevados contenidos en Th y Sc en las fangolitas respecto a la media de UCC (Fig.…”
Section: ) Permite Apreciar Que Las De La Formaciónunclassified
“…Son asimismo positivas las relaciones de Al 2 O 3 con el K 2 O y el MgO (Fig. 15), y las rocas con altos contenidos de esos elementos pueden también reflejar la (Gu et al, 2002) y Cr/Th versus Th/Sc (Condie, 1993;Asiedu et al, 2004) que muestran la ubicación preferencial de las muestras estudiadas en campos correspondientes a rocas ígneas félsi-cas. Valores de referencia para la figura 12B tomados de Totten et al (2000): UCC: corteza continental superior, MORB: promedio de basaltos de dorsales centro oceánicas; C. Diagrama bivariado Zr/TiO 2 versus Nb/Y de clasificación de las rocas volcánicas (Winchester y Floyd, 1977) en el que las muestras de la Formación Vaca Muerta se ubican en el campo de las composiciones intermedias.…”
Section: Geoquímica Y Aportes Terrígenosunclassified
See 1 more Smart Citation
“…The SiOz/Ab03 ratio of the samples is low (3.3-6.7), which is indicative of immaturity. The variable KzO/NazO ratio (0.4-1.2) and average value ofO.8, can be interpreted in the same way (Asiedu et al, 2004;Spaletti et al, 2008). The Rb/Sr ratio, which also reflects recycling processes, varies between 0.15 and 0.88, with an average value of 0.5.…”
Section: Composition and Classificationmentioning
confidence: 99%